Bioremediation of used engine oil contaminated soil by Bacillus salmalaya 139I / Derardja Abdelaziz - Derardja , Abdelaziz (2017)
This study was carried out to test the effectiveness of Bacillus salmalaya strain 139I and its biosurfactant to decontaminate soil using an ex-situ washing technique. The experimental variables include temperature (25, 37, 42 and 55°C), concentration of mixed liquor (0.01, 0.1, 1 and 10%-v/v), volume of mixed liquor (5, 10, 15 and 20 ml), shaking speed (80, 120, 160 and 200 strokes/min) and washing time (5, 10, 15 and 20 min). To determine the most optimal environmental conditions for the treatment, Taguchi Experimental Design Method was applied based on the Orthogonal Array L16' 4˄5. Results showed that the percentage removal of used engine oil ranged from 15.48% to 47.36%. The highest removal of 47.36% can be obtained when washing temperature was at 25°C, with 20 ml of 10% v/v mixed liquor, 200 strokes min-1 shaking speed and 20 min washing time. However, removal equilibrium cannot attained at these maximum points, except shaking speed which indicated maximum removal efficiency at third level (160 stroke/min). Washing time was found to be the most influential variable for the treatment. C/N ratio of 23:1 of contaminated soil sample is within range required to degrade hydrocarbon contaminated soils mentioned in literature. However, after 30 days of treatment the degradation of used engine indicated the need of providing nutrients such as carbon, nitrogen and sulphur, oxygen and water in order to guarantee bacterial growth and acceleration in the degradation rate of contaminants. As 83% of used engine oil degradation achieved in period of only 2 months of treatment, Bacillus salmalaya 139I can be considered as an effective microbe to decontaminate soil.